Analisis Sistem Akuntansi Gaji dan Upah Perum BULOG Cabang Surabaya Selatan - Farihatus Sholihah Farihatus Sholihah; Rachma Agustina (Prodi Akuntansi Fakultas Ekonomi Universitas Hasyim Asy'ari, 2020)
Salary and wages are importan elements that must be considered by the company because it deals with employees. Companies can use salary and wage systems to assist in calculating, recording, and distributing salaries and wages to employees. Object of this research is Perum BULOG Cabang Surabaya Selatan. The aim of this research is to analyze the salary and wage system at the Perum BULOG Cabang Surabaya Selatan. This research is a qualitative descriptive study with a case study approach. Data analysis technique used are collecting and reducing data regarding, then drawing conclusions. The result of the study, the salary and wage system flow chart that are used by the Perum BULOG Cabang Surabaya Selatan includes the system in the human resources section and the payroll system in the financial office headquarters. The system already quite effective, but the salary and wage system used by Perum BULOG Cabang Surabaya Selatan has no the time attendance function is present or the attendance function.